PERENCANAAN TEKNIS SISTEM PENYALURAN DAN PENGOLAHAN AIR BUANGAN DOMESTIK (Studi Kasus : Kelurahan Bojongsalaman Kecamatan Semarang Barat Kota Semarang) - Setya Widiana (Jurnal Teknik Lingkungan, 2013)
Bojongsalaman urban village located on the sewerage system planning whit mid-term or urgent program. This is because there are many puddles of water on the area that can interfere with actifities of the community. Therefore we need a sawerage system that the domestic sewerage system carried by pipeline form the tank to the bulding saptic processing (small bore sewer). For domestic wastewater treatment used sump wells equipped with pumps, initial sedimentation pond, stabilization pond, and collector pond . it is expected that delivery system and treatment of domestic waste water in the Bojongsalaman can reduce sanitation problems and the region can realize a healthy, comfortable and liveable.